Low-Fat Duck Meat Production Through Suplementation Seed Papaya (Carica papaya L.) as Feed Additive - Rachmatika, Rini; Supadmo, Supadmo; Zuprizal, Zuprizal; Prijono, Siti N (LIPI Press, 2014)
Duck meat as a source of animal protein has ahigher fat and cholesterol content than the other poultries. In this case papaya seeds containing tannins, flavonoids, and saponins can reduce the levels of fat and cholesterol content in meat ducks. This research aims to produce low-fat duck meat through the supplementation of various levels of seed papaya as feed additive. This experiment was designed using Completely Randomized Design (CRD) with four treatments: T0 = 0%; T1 = 0.3%; T2 = 0.6%; T3 = 1.2% of papaya seeds in feed. Each treatment has three replications with six ducks in each replicate. Data were analyzed by analysis of variance (ANOVA) using SPSS 16.0 and a Duncan's multiple range test was used to determine the significant difference among the means at 5% level of significance. The results showed that crude fat in breast muscle was significantly decreased from 11.76% +/- 0.58% (T0) to 6.84 +/- 0.22% (T3). Crude fat in legs muscle were siqnificantly decreased from 11. 78 +/-0.47% (T0) to 6.73 +/- 0.56% (T3). Cholesterol in breast muscle was significantly decreased from 64.95 +/- 23.7 mg/100 g (T0) to 34.55 +/- 22.94 mg/100 g (T3). Cholesterol in leg muscles was significantly decreased from 64.86 +/- 13.53 mg/100 g (T0) to 47.49 +/- 14.17 mg/100 g (T3)